PEMBERDAYAAN MASYARAKAT OLEH PEMERINTAH DAERAH KABUPATEN KUANTAN SINGINGI MELALUI PROGRAM PEYEDIAAN AIR MINUM DAN SANITASI BERBASIS MASYARAKAT (PAMSIMAS) DI KECAMATAN KUANTAN HILIR TAHUN 2016-2017 - Adel Andriadi; Ali Yusri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2018)
This research aims to find out the implementation of community empowerment by district government of kuantan singingi through community-based drinking water and sanitation (PAMSIMAS) program at down stream of quantan, in terms of program implementation, program implementation, empowerment effort, training and education implementation, supervision and review and maintenance and improvement of program facilities. this research uses qualitative research methods with descriptive research type that can be interpreted as a problem-solving process in the investigation by describing the state of research subjects based on the facts found. this study found that community empowerment by district government of kuantan singingi through drinking water supply and community-based sanitation program (PAMSIMAS) in downstream kuantan has not been done well, due to lack of people's desire to do maintenance and maintenance of program construction facilities such as sanitation pipe which is leaking and damaged. this is caused the people less involved in the development process, so that people have less sense of ownership of existing facilities and infrastructure Keywords: community empowerment, pamsimas program